Influences of audible radiation‐monitors or radiopaque‐pads on operator and patient dose. Issue 7 (December 2016) - Balter, Stephen
Key Points: Real‐time awareness of their own radiation exposure reduced operator irradiation. The use of radiopaque pads did not significantly reduce operator irradiation. Real or perceived measures that reduce operator risk may bias clinical decisions toward "more complete" procedures and increase patient dose.